The Role Of Streamer Interactivity, Entertainment Value, And Emotional Arousal As Predictors Of Customer Satisfaction In Tiktok Live Commerce: A Study On Gen Z Beauty Products - Ameliya Adisty; Husni Muharram Ritonga; Firman Ario (Jurnal Fokus Manajemen, 2026)
Live commerce via TikTok has become an increasingly dominant digital consumption pattern among Generation Z, especially for beauty products. This study aims to analyze the influence of Streamer Interactivity and Entertainment Value on Customer Satisfaction, both directly and through Emotional Arousal, as well as to examine the role of Product Trust/Engagement as a moderating variable in the context of TikTok Live Commerce for Skintific products. The study uses a quantitative approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. Data were obtained through a questionnaire survey of 384 Generation Z respondents who use TikTok Live Commerce and analyzed using SmartPLS. The results show that Streamer Interactivity and Entertainment Value have a positive and significant effect on Emotional Arousal and Customer Satisfaction. Emotional Arousal was found to mediate this relationship, while Trust/Product Involvement strengthens the effect of Emotional Arousal on Customer Satisfaction. These findings contribute to the development of digital marketing studies based on the S–O–R model and provide practical implications for live commerce strategies.